Pendekatan Komunikatif dalam Pembelajaran Bahasa Arab bagi Non-Arab - Yasmadi Yasmadi (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2013)
Very relevant communicative approach used in language learning as one of the functions of language is to communicate. There are four communicative competence in language learning, namely grammatical competence, sociolinguistic competence, discourse analysis competence and strategic competence. The success of the communicative approach is determined by understanding the function of the language itself and the scope of the communication language.